2020
DOI: 10.1093/femsec/fiaa098
|View full text |Cite
|
Sign up to set email alerts
|

Four decades of soil water stress history together with host genotype constrain the response of the wheat microbiome to soil moisture

Abstract: There is little understanding about how soil water stress history and host genotype influence the response of wheat-associated microbiome under short-term decreases in soil moisture. To address this, we investigated how plant breeding history (four wheat genotypes; two with recognized drought resistance and two without) and soil water stress history (same wheat field soil from Saskatchewan with contrasting long-term irrigation) independently or interactively influenced the response of the rhizosphere, root and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 47 publications
6
63
2
Order By: Relevance
“…Nevertheless, it is important to notice that we used a single pure contaminant in this study, which is rarely the case in nonexperimental conditions. Other studies with this and other plant species have shown the overriding effect of soil characteristics on bacterial communities in a variety of studies, compared to plant characteristics (52)(53)(54)(55). Alternatively, as fungi were shown here and elsewhere to be generally more affected by plant characteristics (47) and identity (56), rhizoremediation based on fungi could be more successful across various soil types.…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, it is important to notice that we used a single pure contaminant in this study, which is rarely the case in nonexperimental conditions. Other studies with this and other plant species have shown the overriding effect of soil characteristics on bacterial communities in a variety of studies, compared to plant characteristics (52)(53)(54)(55). Alternatively, as fungi were shown here and elsewhere to be generally more affected by plant characteristics (47) and identity (56), rhizoremediation based on fungi could be more successful across various soil types.…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, it is important to notice that we used a single pure contaminant in this study, which is rarely the case in non-experimental conditions. Other studies with this aa other plant species have shown the overriding effect of soil characteristics on bacterial communities in a variety of studies, as compared to plant characteristics (Bell et al 2014; Yergeau et al 2009; Azarbad et al 2020). Alternatively, as fungi were shown here and elsewhere to be generally more affected by plant characteristics (Yergeau et al 2015) and identity (Boeraeve, Honnay et Jacquemyn 2018), rhizoremediation based on fungi could be more successful across various soil types.…”
Section: Discussionmentioning
confidence: 88%
“…Two datasets were produced: OTU relative abundance (fraction of total reads) and absolute OTU abundance which was estimated by multiplying the OTU relative abundance matrix by the corresponding abundance of 16S rRNA gene and ITS region obtained by qPCR quantifications, as previously suggested (Zhang et al, 2017;Jian et al, 2020). Since soil history was previously identified as the main factor structuring microbial communities (Azarbad et al, 2018(Azarbad et al, , 2020, we focused on this factor for the needs of our demonstration, but similar conclusions could be reached by focusing on cultivar or SWC effects. To investigate the possible effect of soil history on the relative and estimated absolute abundance of the most abundant bacterial and fungal phyla associated with the rhizosphere of wheat genotypes, analysis of variance (ANOVA) was performed.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Rhizosphere samples were collected (4 wheat genotypes x 2 soil history type x 4 SWHC × 5 replicates = 160 samples) at the end of the experiment (after four weeks of exposure to different soil water content) to measure rhizosphere CO2 emission and microbial community structure. Detailed information regarding sampling sites, the experimental design, CO2 production measurements, qPCR assays, amplicon library construction and sequencing has been previously published (Azarbad et al, 2018(Azarbad et al, , 2020 and is provided as Supplementary Material.…”
Section: Soil Sample Collections and Experimental Designmentioning
confidence: 99%